HIV TAT Protein Transduction Domain Mediated Cell Binding and Intracellular Delivery of Nanoparticles - MacKay, J. Andrew (2003)
Intracellular delivery of non-transported therapeutic agents has traditionally been thought possible only for low molecular weight (<500 DA) hydrophobic molecules. Higher molecular weight agents including oligonucleotides, proteins, DNA, liposomes, and nanoparticles do not readily enter the cytoplasm. However, the human immunodeficiency virus (HIV) trans-acting transcriptional activator (TAT) protein enters the cytosol by way of an 11 amino acid cationic peptide (TATp). When this cationic sequence is attached to a variety of small pharmacological agents, including paramagnetic ions[1,2] and proteins,[3–6] they are delivered into cells. Further, TATp modification of large cargo, such as proteins, polymers, and nanoparticles, may enable them to internalize into cells as well. The size limitations for cargo delivered by a single TATp are currently undetermined, but multiple TATp attached to polymers, nanoparticles, liposomes, and phage can definitely mediate their internalization. This process appears to follow an endocytotic or potocytic pathway and does not directly transfer the cargo into the cytoplasm of the cell. Here we review recent publications in which multiple TATp have been attached to and resulted in the successful intracellular delivery of nanoparticles.